High Energy OFDM Pulse Design Algorithm for Acoustic ToF Ranging and Localization - Albuquerque, Daniel (2017)
This paper proposes an algorithm to design band-limited Orthogonal Frequency Division Multiplexing (OFDM) pulses for accurate time-of-flight ranging in acoustic-based localization systems. The proposed algorithm is capable to generate OFDM pulses with higher energy when compared with other common pulse design approaches with similar characteristics. The results attained have shown that it is possible to design OFDM pulses with 17% more energy than a chirp or a BPSK pulse with the same characteristics. The proposed algorithm uses an iterative approach to increase the pulse energy while keeping the same amplitude, bandwidth and duration in each iteration. Two different OFDM pulses are provided and compared with two common pulses, namely chirp and BPSK pulses, with the same characteristics.